The effect of Islamic work ethic on organisational justice - Rokhman, Wahibur; Hassan, Arif (The Business Ethics Network of Africa, 2012)
The study proposed to investigate the effect of the Islamic work ethic on the perception of justice among employees in Islamic microfinance institutions in Indonesia. The construct of organisational justice included three dimensions, namely distributive, procedural, and interactional justice. The sample consisted of 370 employees from 60 Islamic microfinance institutions in Central Java, Indonesia. The results suggest that the Islamic work ethic positively contributes to the aforementioned three dimensions of the perception of justice. Implications, limitations, and suggestions for future research are discussed.